Integration of prosumer peer-to-peer trading decisions into energy community modelling - Pena-Bello, Alejandro; Parra, David; Herberz, Mario; Tiefenbeck, Verena; Patel, Martin K.; Hahnel, Ulf J. J. (Nature Energy, 2021)
Peer-to-peer energy trading can foster participation in the energy transition, but little is understood about prosumer preferences and their effect on the grid. Pena-Bello et al. use an online experiment among German homeowners to study decision-making strategies and simulate their impact on the operation of an energy community.
CRIS-Team WoS Importer:2021-12-24